A review of interactions between ocean heat transport and Arctic sea ice. (17th November 2021) - Docquier, David; Koenigk, Torben
Abstract: Arctic sea ice has been retreating at fast pace over the last decades, with potential impacts on the weather and climate at mid and high latitudes, as well as the biosphere and society. The current sea-ice loss is driven by both atmospheric and oceanic processes. One of these key processes, the influence of ocean heat transport on Arctic sea ice, is one of the least understood due to the greater inaccessibility of the ocean compared to the atmosphere. Recent observational and modeling studies show that the poleward Atlantic and Pacific Ocean heat transports can have a strong influence on Arctic sea ice. In turn, the changing sea ice may also affect ocean heat transport, but this effect has been less investigated so far. In this review, we provide a synthesis of the main studies that have analyzed the interactions between ocean heat transport and Arctic sea ice, focusing on the most recent analyses. We make use of observations and model results, as they are both complementary, in order to better understand these interactions. We show that our understanding in sea ice - ocean heat transport relationships has improved during recent years. The Barents Sea is the Arctic region where the influence of ocean heat transport on sea ice has been the largest in the past years, explaining the large number of studies focusing on this specific region. The Pacific Ocean heat transport also constitutes a key driver in the recent Arctic sea-ice changes, thus its contribution needs to be taken into account. Although under-studied, the impact of sea-ice changes on ocean heat transport, via changes in ocean temperature and circulation, is also important to consider. Further analyses are needed to improve our understanding of these relationships using observations and climate models.